THE PATTERNS OF KOREAN’S NARRATIVE: BASED ON THE ‘RULE OF THREE’ - KIM, Mansu (International Journal of Korean Humanities and Social Sciences, 2017)
Korea has several conflicting images. The first image was that Korea has been a small and weak country. Korean Peninsula places at the collision point of continents and oceans, so it has been forced to encounter the frequent invasions from other strong neighboring countries. The second image is that Korea is a very interesting and dynamic society which has a long history and excellent cultures. Nowadays Koreans are known to be very smart and excellent in arts and science. Owing to the ardent desire for the children’s education, young Korean students are more educated and talented than those of any other nations. Between the passive belittlement opinion and extremely exaggerated applause, there could be more balanced third opinions suitable for Korean’s position. Korea is trying to confirm its identity through the comparison with other countries; China, Japan, and the United States. China has been the most powerful empire at the center of East Asia. For this reason, Korea chose a voluntary way of submission to China for a long time. Of course, there happened to be a time of resistance as an opponent. Korea sometimes has kept the attitude of "subservience to the stronger" on China. Japan has been considered as a less civilized country than Korea. But it grew to be the most powerful imperialist’s nation in East Asia and dominated Korea as a kind of substantial colony for 35 years. At the beginning of 20th century, the United States emerged as the super power among the all nations. Their power influenced to lots of nations as a police of the world as if they were the only police who can keep world peace. They were the friendly helper to South Korea for a long time. But it is not strange there were some occasional conflicts between the two nations. In general, Korea has chosen a policy of obedience to these powerful countries. But on the contrary of realistic attitude to them, Korean has continuously kept the attitude of independence and resistance in their deep minds. In the folk tale, it is the universal law that the weakest finally wins the strongest. The pattern of Korean’s narratives is same to that folk tale. Koreans feels a kind of empathy to these folk tales for they have been too weak themselves. So they made their own tales based on the contrast between strong and weak. Koreans have felt serious agony against inevitable power between continent/ ocean, China/ Japan, China/ United States. These were the Koreans’ destiny in their daily life. But Koreans developed lots of fictitious narrative which shows the imaginative victory of Korean. The pattern of ‘Rule of three’ can be divided into four; simple or cumulative, progressive or ascending, contrasting or double negative, dialectical. In this paper, I am going to introduce some Korean narratives, which show the victory of the weakest. The stories of General Yushin Kim and Great Monk Samyeong could be chosen the representative examples of Korean narratives. "Three colored national flag" has been used in the world. For example, French people uses three colored flag for the meaning of liberty, equality and fraternity. I guess, in Poland, the legend of ‘three eagles’ could be used for the relationship of Russia, Germany and Poland or Germany, Czech and Poland. Currently, it can be used for the Korean’s dilemma between the powerful Group Two. Koreans are always asking to themselves: which way we must choose to survive between two powerful brothers, what is the third way we can choose as the youngest brother. These questions are making many narratives on Korean themselves.